SPS(Kayexalate)/CPS(K-Bind) crystals in the gastrointestinal tract-An experience from a tertiary center - Divya A Ail; Arjun Prakash; Aditi Damle; Swathi Karottue; Roopa R Paulose (Wolters Kluwer Medknow Publications, 2021)
Introduction: Kayexalate (Sodium Polystyrene Sulfonate/SPS) and K-bind (Calcium Polystyrene Sulfonate/CPS) are cation exchange resins, commonly used for treatment of hyperkalaemia. SPS/CPS induced injury of the gastrointestinal tract(GIT) is rare, can be potentially life threatening but is under-recognized. This study aims to increase awareness of pathologists and clinicians of this under-reported complication of a drug commonly used to treat hyperkalaemia. Materials: Study population comprised patients with SPS/CPS (Kayexalate or its analogues) crystals identified in gastrointestinal specimens from 2017-2019 at a tertiary care centre. Clinical details, relevant investigations, imaging and endoscopic findings, patient follow up details were obtained from the hospital electronic information system. Results: A total of 10 patients with SPS/ CPS crystals in the GIT were encountered over 2 years. Male to female ratio was 9:1, with mean age 66.5years (range 52-82 years). Eight cases were mucosal biopsies and 2 were resection specimens. Additional pathology (tumours, colonic perforation) was present in 80% of patients. The characteristic morphological appearance of the CPS/SPS crystals on H&E stains were supported by special stains -Periodic acid Schiff(PAS) and Acid fast Bacilli(AFB). In all cases, the treatment history with SPS/CPS for hyperkalaemia was obtained only after the histological examination. Most common etiology of hyperkalaemia encountered was chronic kidney disease(CKD)/ Acute on chronic kidney disease. Conclusion: It is important for pathologists to recognise the presence of these crystals especially in small biopsies as early feedback to clinicians can help in appropriate management and avoidance of more serious adverse outcome. To the best of our knowledge, this is the first series of 10 consecutive cases of SPS/CPS crystals encountered in gastrointestinal tract to be reported from India.